Pengembangan E-Modul Bimbingan Kesehatan Reproduksi untuk Mencegah Seks Bebas Di SMK Negeri 3 Makassar - Nahumarury, Marwah (Guidance : Jurnal Bimbingan dan Konseling, 2023)
Development of reproductive healt guidance e modul to prevent free sex at SMK Negeri 3 Makassar. This study aims to describe the needs, produce prototypes, and to determine the validity and practicality of developing reproductive health guidance e-modules to prevent free sex at SMK Negeri 3 Makassar. This type of research is research and development. The research instruments used in this study were interviews and questionnaires consisting of validation questionnaires and trial questionnaires. The data analysis technique is quantitative descriptive analysis. The results showed that in accordance with the conditions at SMK Negeri 3 Makassar, it is necessary to procure reproductive health guidance e-modules to prevent free sex, because this e-module is able to provide convenience and fluency in the guidance and counseling process and is able to be used practically in the process of providing services reproductive health guidance.